Flexibility mechanisms in environmental regulations Their use and impacts - Braathen, Nils Axel (OECD Environment Working Papers, 2019)
Based on an in-depth literature review and responses to a survey among OECD member countries, this paper discusses the use of flexibility mechanisms in environmental regulations. Such mechanisms can provide flexibility as to how a given environmental improvement is achieved, regarding where environmental improvements take place, when they take place, as regards who is to achieve the improvements, and for which pollutants the emission reductions are to be achieved. The literature on these issues is limited, but it is clear that some such mechanisms can have important environmental and economic impacts. In certain cases, flexibility mechanisms which have provided important benefits in terms of cost reductions have proven to also shift pollution to areas where the negative health impacts are larger. Hence, it will be useful to carefully assess the related social costs and benefits of both existing and new flexibility mechanisms